Nitrate Esters Chemistry and Technology - Liu, Jiping (Springer Nature Singapore : Imprint: Springer, 2019)
The idea of this book is to present the up-to-date research results on Nitrate Esters as explosive materials. It covers many aspects including the material structures, nitrating agent, chemical synthesis devices, preparation technology, and applications etc. In particular, this work sheds light on the comprehensive utilization and thorough destruction of the used Nitrate Easters which is crucial for preventing repeated pollution. This is a highly informative and instructive book providing insight for the researchers working on nitrating theory, energetic materials and chemical equipments.